2006
DOI: 10.1016/j.joca.2006.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in immunolocalisation of β-dystroglycan and specific degradative enzymes in the osteoarthritic synovium

Abstract: beta-DG has been shown to have a role in angiogenesis, and our results demonstrate for the first time that there are clear differences in beta-DG staining between OA and control synovial blood vessels. The specific immunolocalisation of beta-DG within endothelium of inflamed OA blood vessels and its co-localisation with MMP-3 and -9, reported to have pro-angiogenic roles and believed to be involved in beta-DG cleavage, may also suggest that beta-DG plays a role in angiogenesis accompanying OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Kahn et al (2000) demonstrated increased ADAMTS-4 mRNA expression in HUVECs differentiating in response to growth factors including VEGF, and detected intense ADAMTS-4 mRNA expression in vascular endothelium in areas of inflammation. However, Wimsey et al (2006) failed to detect immunohistochemical staining of ADAMTS-4 in osteoarthritic synovium. Our data clearly demonstrate the presence of ADAMTS-4 mRNA in isolated HUVECs and HuDMECs, but the quantitative relationship between AD-AMTS-4 mRNA and protein is not known.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Kahn et al (2000) demonstrated increased ADAMTS-4 mRNA expression in HUVECs differentiating in response to growth factors including VEGF, and detected intense ADAMTS-4 mRNA expression in vascular endothelium in areas of inflammation. However, Wimsey et al (2006) failed to detect immunohistochemical staining of ADAMTS-4 in osteoarthritic synovium. Our data clearly demonstrate the presence of ADAMTS-4 mRNA in isolated HUVECs and HuDMECs, but the quantitative relationship between AD-AMTS-4 mRNA and protein is not known.…”
Section: Discussionmentioning
confidence: 91%
“…(2000) demonstrated increased ADAMTS‐4 mRNA expression in HUVECs differentiating in response to growth factors including VEGF, and detected intense ADAMTS‐4 mRNA expression in vascular endothelium in areas of inflammation. However, Wimsey et al. (2006) failed to detect immunohistochemical staining of ADAMTS‐4 in osteoarthritic synovium.…”
Section: Discussionmentioning
confidence: 93%
“…MMP-13 and aggrecanases are over-expressed in the synovial space in many cases of human osteoarthritis (Senolt et al, 2006;Wimsey et al, 2006;Takaishi et al, 2008). Understanding basic signaling pathways of MMP-13 induction may improve therapeutic strategies for chondroprotective therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the 30 kDa b-DG fragment has been reported under different pathological conditions of the skeletal muscle, such as Duchenne muscular dystrophy, Fukuyama-type congenital dystrophy and sarcoglycanopathy (12). The 30 kDa b-DG fragment was also detected in tissues subjected to ischemic injury (13,14) and in joint tissues from patients affected by osteoarthritis (15); finally, b-DG degradation was also discovered in some forms of epithelial cancerous cells (16). In any case, the 30 kDa b-DG fragment lacks all or part of the b-DG ectodomain, as it can be detected using the monoclonal antibody 43DAG directed against the C-terminus of b-DG.…”
Section: Introductionmentioning
confidence: 96%